222k views
5 votes
Evaluate 6 x 3 + (17-3) - 4 Explain your answer

User Kadri
by
6.3k points

2 Answers

4 votes
Hi there!

• 6 × 3 + (17 - 3) -
4

Simplifying. Accr'ding to P.E.M.D.A.S. :-

6 × 3 + (17 - 3) - 4

=> 6 × 3 + 14 - 4

=> 18 + 14 - 4

=> 32 - 4 = 28

Hence,
The required answer is 28

~ Hope it helps!
User TreyBake
by
6.0k points
0 votes
Hi there!

We need to use PEMDAS to simplify.
P = parenthesis
E = Exponents
M = Multiply
D = Dividing
A = Adding
S = Subtracting


6 * 3 + (17 - 3) - 4
Between the parenthesis first.


6 * 3 + 14 - 4
Now multiply.


18 + 14 - 4
Add


32 - 4
Finally subtract.


28
Hence, the answer is 28.

~ Hope this helps you!
User Ufo
by
5.6k points